2019
DOI: 10.2147/ott.s190208
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lipid nanobubbles as an ultrasound-triggered artesunate delivery system for imaging-guided, tumor-targeted chemotherapy</p>

Abstract: Purpose Herein, this study is to prepare folic acid (FA)-conjugated lipid nanobubbles (NBs) that highly load artesunate (Arte; FA-ALNBs), as an ultrasound (US)-triggered Arte delivery system for imaging-guided, tumor-targeted chemotherapy. Materials and methods The morphology, size, zeta potential, and stability of the FA-ALNBs were detected by optical microscopy and dynamic light scattering analysis. The cellular uptake of the FA-ALNBs was evaluated by confocal laser s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The accumulation of TiS 2 -HSA-FA in tumor was likely due to the FA modification, which is known to facilitate tumor targeting. 44,45 As shown in Figure 5C, after intravenous injection, blood distribution half-life (t 1/2 α) and blood terminal elimination half-life (t 1/2 β) of the TiS 2 -HSA-FA were 1.21±0.11 hrs and 17.52±0.62 hrs, respectively. It has been reported that PEG and HSA modifications can prolong blood circulation and reduce macrophage clearance of nanoparticles from the reticuloendothelial system.…”
Section: In Vivo Biodistribution and Blood Circulationmentioning
confidence: 93%
“…The accumulation of TiS 2 -HSA-FA in tumor was likely due to the FA modification, which is known to facilitate tumor targeting. 44,45 As shown in Figure 5C, after intravenous injection, blood distribution half-life (t 1/2 α) and blood terminal elimination half-life (t 1/2 β) of the TiS 2 -HSA-FA were 1.21±0.11 hrs and 17.52±0.62 hrs, respectively. It has been reported that PEG and HSA modifications can prolong blood circulation and reduce macrophage clearance of nanoparticles from the reticuloendothelial system.…”
Section: In Vivo Biodistribution and Blood Circulationmentioning
confidence: 93%
“…Also, the FA-ALNBs did not exhibit any signicant toxic effect. 90 PFB-NBs were co-loaded onto liposomes of less than 300 nm in diameter with a model compound. The subsequent nested-NBs demonstrated strong ultrasonic echo at conspicuous ultrasonic imaging frequencies between 3 MHz and 8 MHz.…”
Section: Ultrasound Combined With Nbs For the Delivery Of Anticancer Drugsmentioning
confidence: 99%
“…Some other recent studies have also shown that NBs have no systemic toxicity in vivo, which is ideal for their future clinical application in anticancer therapy. 113,114 Although the comprehensive safety assessment remains inadequate, this will be the subject of future research. 115 Furthermore, if the use of the nanobubbles is benecial for treatment, then the effort to translate them into clinical applications will be worth it.…”
Section: Potential Safety Concernsmentioning
confidence: 99%
“…Ultrasound (US) technology, due to its non-invasive, non-radiative, low-cost, and specific characteristics, is widely used in clinical diagnosis and tumor treatments [10][11][12]. In recent decades, an acoustic response platform (ARP) with US imaging and therapeutic capabilities has been developed for effective tumor diagnosis and treatment [13][14][15][16]. ARP mainly includes microbubbles or nanobubbles (MB or NB) and nanoparticle (NP) based platforms [16,17].…”
Section: Introductionmentioning
confidence: 99%